Annual Carbon Footprint From Local Electricity Generation in Federal University of Technology, Owerri, Imo State, Nigeria. (November 2022) - Amakom, Chijioke M; Ogungbenro, Oluwasogo A; Iheonu, Nneka O; Nkwoada, Amarachi; Iwueke, David C; Anya, Joseph; Okoye, Joseph
The carbon di-oxide (CO2 ) emissions emanating from the consumption of fossil fuels for generation of electric power in order to sustain the smooth running of activities at the Federal University of Technology, Owerri (FUTO) has been investigated. With appropriate emission factors and the amount of fuel consumption by the generators per annum, the annual CO2 emissions from both diesel and PMS operated electricity generators were estimated. This emission amounted to ~1460.20 tons of CO2 per annum with the institution's diesel generators accounting for ~59%. The several gasoline generating sets scattered across the institution accounts for ~31% of the total CO2 emission. From literature, the result of this study shows that FUTO is one of the highest carbon emitters amongst other institutions were such studies have been carried out. There is a crucial need to control pollution and diversify into renewable sources of energy so as to reduce the carbon footprint emanating from generating power for the institution's use.